Contractile function of detrusor smooth muscle from children with posterior urethral valves – The role of fibrosis. Issue 1 (February 2021) - Johal, Navroop; Cao, Kevin; Arthurs, Callum; Millar, Michael; Thrasivoulou, Christopher; Ahmed, Aamir; Jabr, Rita I.; Wood, Dan; Cuckow, Peter; Fry, Christopher H.
Summary: Introduction: Posterior urethral valves (PUV) is the most common cause of congenital bladder outflow obstruction with persistent lower urinary tract and renal morbidities. There is a spectrum of functional bladder disorders ranging from hypertonia to bladder underactivity, but the aetiology of these clinical conditions remains unclear. Aims and objectives: We tested the hypothesis that replacement of detrusor muscle with non-muscle cells and excessive deposition of connective tissue is an important factor in bladder dysfunction with PUV. We used isolated detrusor samples from children with PUV and undergoing primary or secondary procedures in comparison to age-matched data from children with functionally normal bladders. In vitro contractile properties, as well as passive stiffness, were measured and matched to histological assessment of muscle and connective tissue. We examined if a major pathway for fibrosis was altered in PUV tissue samples. Methods: Isometric contractions were measured in vitro in response to either stimulation of motor nerves to detrusor or exposure to cholinergic and purinergic receptor agonists. Passive mechanical stiffness was measured by rapid stretching of the tissue and recording changes to muscle tension. Histology measured the relative amounts of detrusor muscle and connective tissue. Multiplex quantitative immunofluorescence labelling using five epitope markers was designed to determine cellular pathways, in particular the Wnt-signalling pathway, responsible for any changes to excessive deposition of connective tissue. Results and Discussion: PUV tissue showed equally reduced contractile function to efferent nerve stimulation or exposure to contractile agonists. Passive muscle stiffness was increased in PUV tissue samples. The smooth muscle:connective tissue ratio was also diminished and mirrored the reduction of contractile function and the increase of passive stiffness. Immunofluorescence labelling showed in PUV samples increased expression of the matrix metalloproteinase, MMP-7; as well as cyclin-D1 expression suggesting cellular remodelling. However, elements of a fibrosis pathway associated with Wnt-signalling were either reduced (β-catenin) or unchanged (c-Myc). The accumulation of extracellular matrix, containing collagen, will contribute to the reduced contractile performance of the bladder wall. It will also increase tissue stiffness that in vivo would lead to reduced filling compliance. Conclusions: Replacement of smooth muscle with fibrosis is a major contributory factor in contractile dysfunction in the hypertonic PUV bladder. This suggests that a potential strategy to restore normal contractile and filling properties is development of the effective use of antifibrotic agents. Summary Figure Summary Figure